The external dimensions of the European green deal: The case for an integrated approach - Svea Koch; Niels Keijzer (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
The European Green Deal conveys the EU's ambition to adjust and "green" its economic growth trajectory and become climate-neutral by 2050, as part of its contribution to the Paris Agreement and the Sustainable Development Goals. While being ambitiously pursued within the Union's own borders, the Green Deal also has strong external ramifications, as the EU leaves a tremendous ecological footprint in other parts of the world. The EU has referred to this "external dimension" of the Green Deal without further defining it, and appears to primarily understand it as a reflection of the internal strategies and as a call for the EU's partner countries to follow a sustainable recovery trajectory similar to its own. A number of proposed EU domestic strategies (e.g. biodiversity, blue economy or farm-to-fork) contain chapters on global aspects, yet the EU seems to follow a predominantly sectoral logic to implementing the external dimension of the Green Deal. This approach has certain shortcomings. For one, it creates uncertainty for partner countries on how to adapt to the EU's new rules, regulations and standards, and the extent of EU support for adjusting to this. It also creates a vacuum for member state engagement by means of their economy, finance, climate and foreign policies. Last but not least, it lacks clear governance mechanisms to address potentially conflicting policy objectives and to strive for greater coherence of domestic and external EU policies. Ultimately, the EU needs to define the different external dimensions of the Green Deal and promote an integrated approach. Whereas this applies universally to all partner countries of the EU, we focus in particular on developing countries in this paper. We consider these dimensions to be (1) promoting the Green Deal in bilateral and regional cooperation, (2) ensuring coherence and addressing negative spillovers, both in trade and domestic policies and (3) the EU's global leadership in multilateral fora. Combining those three dimensions and governing them across EU institutions and member states allows for the external response to become an integral part of the EU Green Deal. Such an integrated approach allows the EU to claim leadership vis-à-vis other global powers, make credible commitments in multilateral fora for successful "green diplomacy", and use its market and regulatory power to transform itself and others. In its bilateral relationships, the EU needs to strike a "deal" in the true sense of the word: together formulating and "owning" cooperation agendas that are clear in terms of what is in it for the EU's partners and how the EU will cushion the potential negative adjustment costs of partners. Overall, the EU needs to avoid a "projectisation" of the external dimension of the Green Deal and clarify how the different Commission services and member states aim to work together to deliver the Green Deal, including through its various external policy areas, of which development is just one.
Keywords: 330